Revitalisasi dan Pengembangan Ekonomi Desa Wisata Sidoharjo Samigaluh Kulon Progo - Nurwiyanta, Nurwiyanta; Hasanah, Erni Ummi; Khasanah, Nur; Mulyantari, Enny; Risdiyanto, Risdiyanto (Empowerment : Jurnal Pengabdian Masyarakat, 2021)
This community service program is Program Kemitraan Wilayah (PKW) scheme from the Ministry of Research and Technology / National Research and Innovation Agency, Deputy for Strengthening Research and Development. The location of the devotion in the village of Sidoharjo Samigaluh subdistrict Kulon Progo D.I Yogyakarta. The implementation of PKW was carried out by Janabdara University ( proposing college) in collaboration with AMPTA Tourism High School (partner college) and the Regional Government of Kulon Progo district. Problems that have been identified at the location of PKW service in Sidoharjo village of Samigaluh district of Kulon Progo district include :(1) lack of accessibility to tourist destinations (tourism support infrastructure) ;(2) has not been optimal for creative economic development with the utilization of local resources; (3) The potential of agricultural products has not been optimized; (4) Art, culture still needs to be accompanied and optimized. The realization of the devotion program includes the construction of footpaths and safety fences to the top of Gunung Kendil, the creation of selfie spots (self-photos), the construction of gazebos. In addition, training and practice are also carried out for the development of the creative economy (culinary sector) namely by making various snacks that utilize local ingredients, namely taro, cassava, and Regedek leaves. In the field of culture is carried out rejuvenation a set of gamelan. In this service program, socialization is also carried out about the PIRT licensing process for people who already have many household businesses (home industry).